Detergent and Soaps Adulteration Detection in the Milk Using Artificial Embedded Sensors - B S, Rajashekhar; Kusagur, Ashok (International Journal of Engineering and Technology, 2018)
An absolute natural world mammals food is milk and is the only foodstuff that practically consists of almost all the nutrition is known to be necessary for individual personality. This research paper aims to play a good role in the rural source of revenue and livelihood improvement in emergent countries. In an insightful and sustainable way, through assisting the milk provider and consumer factions with harmless reasonably priced milk and dairy foodstuffs. The target of this research paper is to analyze and detection of frauds which are mixing the soapy and detergent materials to the milk for monetary benefits. It will be working on small-scale milk collection. For avoiding adulteration it is aimed to develop an artificial embedded system to discourage farmers and adulterator from adding soaps, detergents and shampoo substances to the milk and the payment scheme should be decided accordingly. An experiment was conducted for pure pasteurized cow milk of 3.5% fat under different temperature conditions on different days. There are 50 experiments with 10 different quantities of adulterants of shampoo, detergents and soaps were conducted. The conducted experimental results were tabulated and analyzed by statistical methods. These experimental results showing that there was no match of conductivity and pH values of the shampoo, detergents adulterated milk with standard pasteurized milk. This mismatch value indicates the presence of adulterants and experimental results show the mixing of detergents leads to the milk pH scale to base range and conductivity may be decreased or increased but never match with the standard pH and conductivity scale. For this reason, it is an efficient and effective method of detection of detergent based adulteration in milk and it is a low-cost design due to low-cost artificial embedded tongue system.Â Â Â